2012
DOI: 10.1371/journal.pone.0040952
|View full text |Cite
|
Sign up to set email alerts
|

Sickness Absence following Coronary Revascularisation. A National Study of Women and Men of Working Age in Sweden 1994–2006

Abstract: BackgroundEvidence based and gender specific knowledge about sickness absence following coronary revascularisation is lacking. The objective was to investigate sickness absence after a first coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) among women and men in a national Swedish study.Materials and MethodsAll patients 30–63 years of age, who underwent a first CABG (n = 22,985, 16% women) or PCI (40,891, 22% women) in Sweden between 1994 and 2006 were included. Information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…Early and active collaboration with occupational healthcare physicians and rehabilitation could be potential targets for improving later working capacity in young patients. Gender did not independently influence the risk of disability unlike the earlier literature on disability in general and after PCI (35)(36)(37). Remarkably even the higher baseline disease burden among women in the present study (data not shown) did not alter the incidence of PWD.…”
Section: Discussioncontrasting
confidence: 85%
“…Early and active collaboration with occupational healthcare physicians and rehabilitation could be potential targets for improving later working capacity in young patients. Gender did not independently influence the risk of disability unlike the earlier literature on disability in general and after PCI (35)(36)(37). Remarkably even the higher baseline disease burden among women in the present study (data not shown) did not alter the incidence of PWD.…”
Section: Discussioncontrasting
confidence: 85%
“…Similar associations have been found for patients who have had a CABG [3][7] or PCI [7]. These studies have in most cases included small, selected patient groups and incomplete follow-up, particularly because outcome data in many studies were collected by questionnaire.…”
Section: Introductionmentioning
confidence: 53%
“…Low SEP has predicted lower rates of return to work in most other studies [3][5], [7]. This might reflect that high SEP jobs are more flexible with regard to taking changes in work capacity into account and that work ability in low SEP jobs is more affected by ACS than in high SEP jobs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, such patients are less responsive to accomplish healthy lifestyle changes post-MI than those with a higher socioeconomic status [3]. Return to work is complicated and prolonged sick leave is common in cardiac populations [4,5]. Cardiac rehabilitation is a multifaceted intervention that includes psychosocial and educational counselling as well as exercise training, which are associated with a reduction in the risk of recurrent MI and mortality, as well as sustained improvements in health-related quality of life [6].…”
Section: Introductionmentioning
confidence: 99%